ANALISA STATISTIK HASIL UJI KAPASITAS METODE DINAMIS (PDA TEST) PADA PONDASI TIANG PANCANG SISTEM PANCANG TEKAN - Haryadi, Didik; Prakoso, Widjojo Adi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The use of HSPD (Hydraulic Static Pile Driver) in deep foundation can reduce the level of noise and vibration as a result of pile driving. When a pile is hydraulically driven into the ground to the required axial compression capacity as recorded by a manometer installed on the HSPD equipment, a failure in this capacity is frequently observed after a dynamic verification test (PDA test). The purpose of this study is to determine the root cause of discrepancies in the axial compression capacity between results monitored by the HSPD equipment and dynamic test verification. This research examined SQ25 and SQ30 piles of 295 and 94 numbers respectively in the period of January 2020 to July 2022. Dynamic verification test indicated that 11% SQ25 and 7% SQ30 piles were problematic. Based on the linear regression analysis, the embedment of pile (Lp), final settlement (DFN), and frictional resistance (Rs) contribute an effect on the mentioned above discrepancy. For the problematic SQ25 and SQ30 piles, values of Ì…Ì…Ì… and Ì…Ì…Ì…Ì… Ì…Ì…Ì… are less than the ones for non-problematic piles. In contrary, the value of Ì…Ì…Ì…Ì…Ì…Ì… for problematic piles is larger than the one for non-problematic piles.